THE RELATIONSHIP BETWEEN NEED FOR ACHIEVEMENT AND LEARNING BEHAVIOR IN YOUTH: A META-ANALYSIS - สิปิยารักษ์, วรนุช; พันธุมนาวิน, ดุจเดือน; พันธุมนาวิน, ดวงเดือน (Thai Interdisciplinary and Sustainability Review, 2024)
The aim of this study is to investigate the relationship between youth's need for achievement and study behavior. Researchers utilize a meta-analysis method to determine the magnitude or effect size (d) of the relationship between variables. The research population consists of research papers, dissertations, and articles. In this study, the independent variable is the need for achievement, while the dependent variable is young people's study behavior. The sample group has a total of 15. The study revealed a positive correlation between the need for achievement and study behavior, with an influence rate above 0.50 across all groups (d = .947). The effect size of the influence between the need for achievement and study behavior was greater than 0.50. This result appeared in all the study's moderating variable subgroups (gender, education level, father’s education and mother’s education). Research shows that the need for achievement variables reflects an important factor in study behavior. Moreover, research shows that the educational backgrounds of both highly educated fathers and mothers influence the academic achievement of successful children in school or university.